Technology, the internet, and social networks in the lives of children and adolescents - Hernández López, José Jhonatan (2018)
The author of this presentation is a teenager who from his own perspective shares his vision to world how technology and social networks influence the family, the role of the parents and especially the childrn and teenagers.